Natural cures for breast cancer treatment - Munazza Shareef (Elsevier, 2016)
For centuries, herbs and plants have been used for medicinal purposes and as food as well. This review concerns about different types of plants that retain the immune stimulating and anti-tumor properties. Large variety of active phytochemicals such as carotenoids, flavonoids, ligands, polyphenolics, terpenoids, sulfides, lignans and plant sterols has been identified in different types of herbs. These phytochemicals have different mechanisms of action. They either stimulate the protective enzyme like glutathione transferase or prevent the cell proliferation. This review has centered on the biochemical properties of Allium sativum, Echinacea, Curcuma longa, Arctium lappa, Camellia sinensis, Panax ginseng and Flax seed. Extracts and juices of Withania somnifera, Amoora rohituka, Dysoxylum binectariferum and Vaccinium macrocarpon, respectively also used as anti-breast cancer. The volatile oils and extracts of these herbs and plants inhibit the synthesis of mevalonate that lessen the tumor growth and cholesterol synthesis.